Understanding the Customers' Acceptance of Pick-up Apps Over the COVID-19 Pandemic Period, Stay-at-Home Orders: An Integrated Model of UTAUT - Atleiya Julianita; Viany Utami Tjhin (Universitas Ahmad Dahlan, 2021)
Current technological developments allow online sellers to request pick-ups via mobile apps. During the COVID-19 outbreak and with the stay-at-home orders, a survey in Indonesia showed that online transactions are increased, which led to the rise of pick-up and delivery activities. However, the pick-up order cancellation possibly happens, bad reviews appear, and apps abandonment can not be avoided. The purpose of this study is to examine user acceptance of the pick-up apps and observe its correlation with the COVID-19 stay-at-home orders using the Unified Theory of Acceptance and Usage of Technology (UTAUT) model with subjective norm to stay at home from the Theory of Planned Behavior (TPB) model as an additional variable. The sample was obtained from 205 users of one of the pick-up apps in Indonesia through a structured questionnaire based on a five-point Likert scale. The results showed that the stay-at-home order due to the impact of the COVID-19 pandemic affects customers’ intention to use pick-up apps and performance expectancy and social influence. Then, the non-linear UTAUT variables influence each other, which is the effect of effort expectancy and social influence on performance expectancy. Finally, the main factor influencing the use behavior of pick-up apps is behavioral intention. This study can contribute to IS research on technology acceptance and provides an overview of customer behavior using the pick-up apps from a pick-up service provider viewpoint.